Family Regenerative Typology of Cianjur Earthquake Survivors: Influence Analysis to Religiosity and Family Vulnerability - Kumalasari, Berti; Sunarti, Euis; Yuliati, Lilik Noor; Herawati, Tin (International Journal of Disaster Management, 2024)
Indonesia is one of the countries prone to disasters. One of the biggest disasters in 2022 was the earthquake in Cianjur Regency. Disaster events result in damage to assets and infrastructure and hamper social growth. This study aims to analyze the differences in religiosity, family vulnerability and regenerative typology between families in lightly damaged and severely damaged houses and analyze the influence of religiosity and family vulnerability on the regenerative typology of earthquake survivor families in Cianjur Regency. The population of this study is the families of earthquake survivors in Cianjur Regency. Respondents in this study were 100 wives with lightly damaged houses and 100 wives with severely damaged houses. Data were analyzed using a statistical package for the social sciences and structural equation modeling least squares. The t-test results showed a higher vulnerability of families in severely damaged houses than families in lightly damaged houses. The regenerative typology of disaster survivor families is influenced by religiosity and family vulnerability. Stakeholders are expected to work together to provide material and psychosocial disaster assistance. It is essential to conduct socialization and education for families to become regenerative and resilient families facing disasters